2005
DOI: 10.1080/03081060500120282
|View full text |Cite
|
Sign up to set email alerts
|

Technical Feasibility of Advanced Driver Assistance Systems (ADAS) for Road Traffic Safety

Abstract: Technical feasibility of advanced driver assistance systems (ADAS) for road traffic safety.Lu, Meng; Wevers, Kees; Heijden, Rob Van Der General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(59 citation statements)
references
References 13 publications
0
59
0
Order By: Relevance
“…Values for ε ki need to be estimated based on expert knowledge. For this it may help to use the four behaviour influence or compulsiveness levels that are generally distinguished for ADAS based on the feedback model that is chosen: information (visual or acoustic), warning (acoustic or haptic), overrideable control (haptic throttle) or non-overrideable control (fuel supply control, gear change and/or braking) (Lu et al, 2005). Although the four compulsiveness levels are clearly derived from ADAS functions, they may be applied to infrastructure measures as well.…”
Section: Methods For Comparative Analysis Of Measures Of Different Naturementioning
confidence: 99%
See 1 more Smart Citation
“…Values for ε ki need to be estimated based on expert knowledge. For this it may help to use the four behaviour influence or compulsiveness levels that are generally distinguished for ADAS based on the feedback model that is chosen: information (visual or acoustic), warning (acoustic or haptic), overrideable control (haptic throttle) or non-overrideable control (fuel supply control, gear change and/or braking) (Lu et al, 2005). Although the four compulsiveness levels are clearly derived from ADAS functions, they may be applied to infrastructure measures as well.…”
Section: Methods For Comparative Analysis Of Measures Of Different Naturementioning
confidence: 99%
“…For speed assistance a sophisticated flexible system layout is assumed that differentiates according to road type and traffic safety requirements: (1) mandatory full control on roads and crossings with mixed traffic; (2) mandatory overrideable control (haptic throttle) on single carriageway roads with separation of traffic categories; (3) voluntary warning on dual carriageway roads specifically designed for motor vehicles. For lane keeping assistance the use of magnetic tape (based on magnetic lane markers) is assumed, which can be used in combination with the normal white lane markers, which nowadays are often also applied in the form of tape instead of the traditional painting (Lu et al, 2005). It should be noted that the values for E 1I and E 2I are based directly on SWOV data, while the values of E 1A and E 2A are derived from these values using formula (10).…”
Section: Methods Illustrationmentioning
confidence: 99%
“…The issue has been discussed in several studies including Marchau and van der Heijden (2000), Marchau and Walker (2003), van der Heijden and Marchau (2005) and Lu et al (2005). In the study by Marchau and Walker (2003), an integrated approach was proposed with respect to ADAS implementation.…”
Section: Adas Implementationmentioning
confidence: 99%
“…As discussed in Lu et al [4], five ADAS functions, that is navigation system with additional functionality [including traffic message channel (TMC)], speed assistance, lane keeping assistant, collision avoidance and intersection support, have been identified that can match infrastructure measures. These functions are either available on the market today or under development or deployment.…”
Section: Identification Of Scenarios For Improving Road Traffic Safetymentioning
confidence: 99%
“…These systems support or take over vehicle driving tasks by sensing, communication and actuating devices and are meant to improve the safety, efficiency and comfort of driving. In previous parts of our research, five candidate ADAS functions are selected, which might meet the DVI requirements [3], and their technical feasibility is analysed [4]. Some state-of-the-art technologies are mature like navigation and speed assistance.…”
mentioning
confidence: 99%